2021
DOI: 10.3390/ijerph18052424
|View full text |Cite
|
Sign up to set email alerts
|

Biodecolourisation of Reactive Red 120 as a Sole Carbon Source by a Bacterial Consortium—Toxicity Assessment and Statistical Optimisation

Abstract: The application of microorganisms in azo dye remediation has gained significant attention, leading to various published studies reporting different methods for obtaining the best dye decolouriser. This paper investigates and compares the role of methods and media used in obtaining a bacterial consortium capable of decolourising azo dye as the sole carbon source, which is extremely rare to find. It was demonstrated that a prolonged acclimation under low substrate availability successfully isolated a novel conso… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
10
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 23 publications
(10 citation statements)
references
References 56 publications
0
10
0
Order By: Relevance
“…As previously, the adjusted coefficient of determination (R 2 ), accuracy factor (AF), bias factor (BF), Root-Mean-Square Error (RMSE), and corrected AICc (Akaike Information Criterion) were used to calculate the statistically significant difference between the models [29,[39][40][41][42].…”
Section: Discussionmentioning
confidence: 99%
“…As previously, the adjusted coefficient of determination (R 2 ), accuracy factor (AF), bias factor (BF), Root-Mean-Square Error (RMSE), and corrected AICc (Akaike Information Criterion) were used to calculate the statistically significant difference between the models [29,[39][40][41][42].…”
Section: Discussionmentioning
confidence: 99%
“…It was also demonstrated that the microbial community comprised of different bacterial classes can partially degrade azo dyes in the absence of an external carbon source [205], while the bacterial consortium comprised of Pseudomonas aeruginosa strain MM01, Enterobacter sp. strain MM05, and Serratia marcescens strain MM06 could use Reactive Red 120 as a sole carbon source [206] The addition of carbon sources can also increase the rate of dye decolorization and degradation. This was shown in a study of Saranraj et al, (2018), wherein the decolorization rate of different azo dyes (Reactive Orange 16, Reactive Black B, and Reactive Yellow MR) increased for various isolates, namely Bacillus odyssey, Bacillus thuringiensis, Bacillus subtilis, Bacillus cereus, Alcaligenes sp., and Nocardiopsis alba, when sucrose was added [207].…”
Section: Mediators and Varying Energy Sources For A More Efficient Dy...mentioning
confidence: 99%
“…Reactive Red 120 (RR120), a type of azo dye (approximately 9.9 million tons used per year) 1 with a complicated organic structure, has been extensively used in the textile industry 2 because the chemical, biological, and photocatalytic stability is very high. Due to these stable and durable properties, the degradation of RR120 by exposure to sunlight, detergents, water, and microorganisms is very difficult.…”
Section: Introductionmentioning
confidence: 99%